THE STRATEGIC ROLE OF COMMUNICATION AND NEGOTIATION - Geovana-Albertina ZOICAN (Social Sciences and Education Research Review, 2025)
This article explores the perceptions, attitudes, and practices surrounding negotiation and communication through an applied sociological survey distributed to a sample of 50 individuals of various ages and professional backgrounds. Through a reformulated and modernized questionnaire, the study investigates styles of negotiation, emotional intelligence, communication preferences, and the impact of digital environments. The findings confirm that while most participants recognize the importance of negotiation and communication, many feel underprepared, especially in managing nonverbal and emotional dynamics. The research advocates for the practical development of communicative competence through education and training.